Re-Designing Sign System in Kiaracondong Railway Station Bandung - Ruth Dina Mentari Hutasoit; I Dewa Alit Dwija Putra (Wimba : Jurnal Komunikasi Visual, 2014)
Sign system is a media information that help people to find their way or destination in an environment. Good sign system can be understood by viewer through the information and visualization indeed. Some of public location that craves sign system is a railway station. However as a high accessibility place, actually railway station has many activities in there, like to buy tickets, waiting for the train, obtaining information operational and others. All of that are needed sign system. Kiaracondong Railway Station as one of well known stations in West Java that had plenty visitors. But, the media information like sign system in there is not yet enough to fulfill the visitors requirement, such as some of them are broken, unsupported materials, the visibility and letter size are not standard measure, and minimum quantity sign system.For more clearly this case, it will be required to aggregation and review the data. Actually, the methods that to be used such as directly observation to station area, collecting theoretical data, share some questionnaire to visitors, make an interview to officers, comparing with several similar projects, and matrix analysis.So based on the situation and data management, we need to redesign the sign system with good integration in Kiaracondong Railway Station for help visitors in railway station to acquire their needs like informations and navigations. In other goal, the redesign sign system can be increase the image of PT KAI in business transportation.